Problematic Issuance of Land Rights Certificate - Moh Ali Wafa (Jurnal Cita Hukum, 2017)
Many people who have not registered ownership rights so that they have no protection andlegal certainty due to several factors: First, factor of land ownership history. Second,community psychology. Third, weakness of land registration rules. Fourth, executorimplementation, intervention BPHTB legislation and other fees. Fifth, the mechanism ofregistration of land is too expensive for the community both procedure and registration fee.The Solution and effort to minimize the occurrence of land disputes society are: first, bypreventing the land dispute case is not repeated. Second, the government immediatelysocialize what and how the issuance of land certificates and the purpose of certificates. Third,If there is dispute in the court that the object is not certified land, the court notifies the urbanvillage and local BPN to block the transaction or the transition of the land immediately. Fourth,each transaction or transition of land with proof of ownership in the form of girik, the witness inthe transaction should be the Village Head and the BPN officer, and fifth, it is better if there island dispute in the court, at least one judge from land law expert, such as non-academicjudges (academics). DOI: 10.15408/jch.v5i2.7089